Inhibitory activities of mushroom tyrosine and DOPA oxidation by plant extracts - Momtaz, S.; Lall, N.; Basson, A. (South African journal of botany, 2008)
Pigmentation has become an important phenotypical characteristic, in the pharmaceutical, medicinal as well as in the cosmetic field. Plants and their extracts are inexpensive and rich resources of active compounds that can be utilized to inhibit tyrosinase activity as well as melanin production. Natural and synthetic chemical agents can frequently modulate the metabolism of pigmentation produced. Methanol extracts of seven plants were evaluated for their inhibitory effect on the monophenolase and diphenolase activated forms of tyrosinase in vitro. Active extracts were also investigated for their inhibitory effect on melanogenesis in B16 melanoma cells. Extracts of Hyaenanche globosa and Myrsine africana showed 92% and 83% inhibition of tyrosinase activity and 42% and 62% inhibition of DOPA auto-oxidation at 500 μg/ml respectively. Rooibos tea which is known for its antioxidant activity did not show any inhibition of tyrosinase or DOPA oxidation activity. M. africana demonstrated 16% and 18% inhibition of melanin production at 6.25 and 12.50 μg/ml respectively.